A rapid and inexpensive molecular technique to discriminate the north-eastern Atlantic and Mediterranean Atherina species and its potential applications in ecology and larval identification - Carvalho Almada, Vítor (2019)
This note describes a rapid and inexpensive Restriction Fragment Length Polymorphism technique to discriminate all species of Atherina (Pisces: Atherinidae) of the north-eastern Atlantic and the Mediterranean. This technique is based on digestion of a fragment of the 12S ribosomal RNA (12SrRNA) gene region of mitochondrial DNA with restriction enzymes that recognize species-speciﬁc nucleotide sites. The three currently recognized species in the area, as well as two additional forms awaiting formal description, can be discriminated using a set of four endonucleases. We argue that this simple and fast technique may be of great help in the identiﬁcation of young stages and in ecological surveys.